O apego ao lugar numa vila piscatória em transição: A relação dos habitantes da Fuzeta com a Ria Formosa - Marques,João Filipe (2021)
Abstract The main objective of this article is to understand the relationship that the residents of Fuzeta, a fishing village in southern Portugal, establish with the Ria Formosa Natural Park, through the concept of place attachment. Recent studies on the relationship between individuals and places highlight the importance of this place attachment, but despite its abundant use, it remains in a stage of theoretical underdevelopment. Furthermore, the lack of research on the attachment to Portuguese Natural Parks endowed this research with an exploratory character and led to the need to a new definition of the concept of place attachment and to the construction of a broader analytical model. The attribution and maintenance of meanings and values to the places, implies not only the relationship of people with the physical elements of the territory but also the interactions of individuals with each other, their sharing of history and culture, and other aspects that can either strengthen or weaken people’s attachments to places. We propose in this article a new analytical model that includes, at the same time, the factors that participate in the attribution of meanings and values to places, and also those that participate in the place attachment process whether in a contributory way or in a disruptive way. The empirical study presented in this article adopted a qualitative interpretative methodology through the use of semi-structured in-depth interviews. Thus, 26 Fuzeta residents engaged in leisure or professional activities in the Ria Formosa lagoon were interviewed. The interviewees were workers from several professional activities that use the lagoon - such as fishermen and shellfish catchers, restaurant and hospitality workers, as well as those engaged in leisure activities such as sunbathing, recreational fishing, the catching of shellfish and crustaceans, hiking, boating, windsurfing and camping. The results indicate that the inhabitants of Fuzeta have a very strong and multidimensional attachment to the Ria Formosa that is related to the meanings, emotions, feelings they attribute to it and mainly to the perception of its irreplaceability.